Effect of TMT process on the strength and precipitation behavior of an 11Cr-0.3Mo-1.6W steel during long term aging - Song, S.M.; Jung, W.S.; Hong, S.W.; Bae, D.S.; Chung, S.H.; Kwun, S.I. (Key Engineering Materials, 2007)
The effect of thermo-mechanical treatment (TMT) process on the strength and precipitation behavior of an 11%Cr-0.3Mo-1.6W steel during long term aging was investigated. The major precipitates in as-tempered specimen were identified as M23C6 (M=Fe,Cr) and MX (M=Ta,V;X=C,N). The M 23C6 precipitate in TMT sample was more finely distributed due to the increased heterogeneous nucleation sites at dislocations. The tensile strength of TMT sample is higher than that of the conventional heat treatment (CHT) sample in as-tempered condition. However, Laves phase starts to precipitate additionally in the aged condition. The growth rate of Laves phase in TMT sample is much faster than that in CHT sample. Therefore, the difference in tensile strength between CHT and TMT sample decreases as the aging time increases.